Peculiarities of the “professional income tax” tax regime - R. Sh. Abakarova (Вестник университета)
In the context of the widespread introduction of a tax on the self-employed in Russia, there is a need for a conceptual understanding of its role in the economic activity of citizens and the development of regions. In this regard, the article considers the results of its introduction in 2019 and the prospects for further development up to 2029. The article reviews the main aspects of the functioning of the new tax regime in relation to the professional income of the self-employed population in the Russian Federation, which were introduced by Federal Law No. 422-FZ dated on November 27, 2018 in a number of regions of the country. The paper explains the main characteristics of the tax and the procedure for its application. The study summarizes preliminary results of the functioning of the new special tax regime under the experimental conditions.